The large-cap portfolio : value investing and the hidden opportunity in big company stocks - Villalta, Thomas, 1970- (Bloomberg financial series., 2012)
The practical guide to finding value and opportunity in large-cap stocks using investor behaviorLarge-Cap is an abbreviation of the term "large market capitalization" and refers to the stock of publicly traded companies with market capitalization values of roughly more than 10 billion, like Walmart, Microsoft, and Ford. Because of their size, the conventional view is that these companies do not present investors with an ability to be opportunistic. The Large-Cap Portfolio + Website argues that, contrary to popular perceptions, significant opportunities exist in these stocks. Written with a flue.